199k views
5 votes
-3(n+8)=3 solve for n

User Tkachuko
by
5.6k points

2 Answers

4 votes

-3(n+8)=3

mutiply the bracket by -3

(-3)(n)= -3n

(-3)(8)=-24

-3n-24=3

move -24 to the other side

sign changes from -24 to +24

-3n-24+24= 3+24

-3n= 3+24

-3n= 27

divide both sides by -3

to get +n

to get n by itself

-3n/-3= 27/-3

Answer:

n= -9

User Laurisvr
by
5.1k points
2 votes

Hey there!

-3(n + 8) = 3

-3(n) - 3(8) = 3

-3n - 24 = 3

ADD 24 to BOTH SIDES

-3n -24 + 24 = 3 + 24

CANCEL out: -24 + 24 because it gives you 0

KEEP: 3 + 24 because it helps solve for the n-value

NEW EQUATION: -3n = 3 + 24

SOLVE ABOVE

-3n = 27

DIVIDE -3 to BOTH SIDES

-3n/-3 = 27/-3

CANCEL out: -3/-3 because that gives you 0

KEEP: 27/-3 because it gives you the result of the n-value

NEW EQUATION: n = 27/-3

SIMPLIFY IT

n = -9

Therefore, your answer is: n = -9

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

User Ian Danforth
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.